The Qualitative Determinants of Financial Failure in SMEs in Morocco. Case of SMEs in Casablanca-Settat Region - BOUTFSSI, Adil; ZIZI, Youssef; QUAMAR, Tarik (Theoretical and Practical Research in Economic Fields, 2025)
In the context of this scientific study, our objective was to contribute to the understanding of the financial failure of SMEs in Morocco to their bank creditors, with a particular focus on the Casablanca-Settat region. Our research focuses on the primary objective of the empirical identification of qualitative factors that impact this phenomenon, greatly threatening a particularly significant number of SMEs. To achieve this objective, a target population consisting of 158 SMEs from the Casablanca-Settat region was selected. Contingency and binary logistic regression analyzes revealed that specific characteristics of SMEs, such as the nature of their activity, competition from the informal sector and their size, as well as the characteristics of the SME leader, such as their previous professional experiences and their skills in management or financial management, play an important role in explaining the financial failure situation of SMEs in this region. The conclusions of this study could be of paramount importance for banking institutions, taking into account the explanatory variables of default when evaluating credit applications, or ensuring careful monitoring of the situation of already affiliated SMEs. The conclusions of our study could also be beneficial for SME leaders in Morocco, as they would allow them to anticipate upcoming financial difficulties and implement corrective actions to avoid a financial distress.